2022
DOI: 10.3389/fimmu.2022.1032280
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase 1 signaling orchestrates immune tolerance in Echinococcus multilocularis-infected mice

Abstract: The cestode Echinococcus multilocularis larva infection causes lethal zoonotic alveolar echinococcosis (AE), a disease posing a great threat to the public health worldwide. This persistent hepatic tumor-like disease in AE patients has been largely attributed to aberrant T cell responses, of which Th1 responses are impeded, whilst Th2 and regulatory T cell responses are elevated, creating an immune tolerogenic microenvironment in the liver. However, the immune tolerance mechanisms are not fully understood. Dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Splenocytes were purified by referring to the previous method ( 25 ). The mice not infected with E. multilocularis were sacrificed, and the spleens were separated in a clean bench, washed with pre-cooled physiological saline, then cut into small pieces, and mechanically dispersed by using a sterile syringe plunger to force through a 70-μm cell strainer to obtain splenocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Splenocytes were purified by referring to the previous method ( 25 ). The mice not infected with E. multilocularis were sacrificed, and the spleens were separated in a clean bench, washed with pre-cooled physiological saline, then cut into small pieces, and mechanically dispersed by using a sterile syringe plunger to force through a 70-μm cell strainer to obtain splenocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research underscores the paramount significance of hepatocyte-expressed IDO1 in fostering the immunological tolerance of the liver. 42 IDO1 is expressed by many cell types, especially macrophages. 43 IDO1 can affect the progression of fibrosis in the liver.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Numerous studies have demonstrated that IDO is expressed by cancer cells themselves as well as by cells surrounding the tumor including macrophages, myeloid derived suppressor cells and even fibroblasts [48]. IDO is also found in other states of immune evasion such as in the tuberculosis granuloma [49], in parasitic infections [50], and in testicular immune privilege [51].…”
Section: Indolamine 23 Dioxygenasementioning
confidence: 99%